Examining heterogeneity : A systematic review of quantitative person-centered studies on adversity, mental health, and resilience in children and young adults with refugee backgrounds - Andersson, Johan; Kankaanpää, Reeta; Peltonen, Kirsi; Münger, Ann-Charlotte; Korhonen, Laura (Elsevier, 2025)
Background
Child and young adult refugees are a heterogeneous group comprising both vulnerable and resilient individuals. Person-centered statistical methods could help disentangle this heterogeneity, enabling tailored interventions. This systematic review examined person-centered studies on adversity, mental health, and resilience in children and young adults with refugee backgrounds to identify subgroups and assess their theoretical and practical relevance.
Methods
Studies were identified through searches of PubMed, Academic Search Complete, Scopus, PsycINFO, CINAHL, ERIC, and Cochrane. The search included all published studies until December 2023. Studies were eligible for review if they used adversity, mental health or resilience variables as indicators in a person-centered analysis. The study population needed to have a refugee background with a mean age of ≤25. The reporting quality of the studies was assessed using the adapted version of the Guidelines for Reporting on Latent Trajectory Studies (GRoLTS) checklist. The results were analyzed in a narrative format and using summary tables.
Results
A total of 6706 studies were initially identified, of which seven were eligible for review. The studies included 2409 individuals and were conducted in refugee camps, communities, and institutional and clinical settings across Africa, the Middle East, Europe, Asia, and North America. Five of the seven studies included adversity as an indicator, and three articles mental ill-health. Only one article specifically investigated resilience. All studies identified subgroups, but the findings regarding predictors of group membership were inconclusive. Risks for adverse outcomes, such as mental health problems, also varied across subgroups. The studies generally displayed inadequate reporting of important methodological aspects of the data analysis, a lack of theoretical consideration, and an absence of reliability testing.
Conclusions
The use of person-centered approaches in research on children and young adults with refugee backgrounds, focusing on adversity, mental health, and resilience, is currently limited. Nevertheless, the reviewed studies provided valuable insights into subgroups within this population, indicating that person-centered approaches can be employed when studying this group. Future research should consider theory and prior knowledge in the selection of the final number of groups, thoroughly report quality criteria, and rigorously test the reliability of classes.